Review: Hydrocephalus and Autism and Occupational Therapy Results, A case Report - Fatemeh Vojdani; Fatemeh Behnia (Journal of Rehabilitation, 2010)
This is a case report. In this essay, a 4years old boy with "Hydrocephalus and Autism" is presented, who referred to an occupational therapy clinic by a psychiatrist and received occupational therapy interventions. Hydrocephalus together with Autism had caused to severe cognitive, perceptual, motor, communicative and self care problems. Occupational therapy goals were facilitation of development in different areas and making adaptive behavior.finally, his difficulties and dysfunctions decreased noticeably : his eye contact was improved seriously , he could keep almost good communication with his family , hyperactivity and aggressive behaviors are decreased, he could draw simple paintings, could run and ride tricycle. By continued rehabilitation interventions, ultimately he could begin studying in one of Tehran normal state schools. The last following up showed that he could passed fifth level of elementary successfully ( with average, 17 ), and now is ready to go to the guidance school. Results of this study show the importance of careful and all-around evaluation of hydrocephalus children, careful combination of therapeutic interventions, cooperation and coordination of all rehabilitation team members, continued following up clients even after discharge, and attracting active cooperation of child parents in occupational therapy successful process.